Influence of spacings, densities and plant height on the performance of grain sorghum - Bueno, Álvaro (Pesquisa Agropecuaria Brasileira, 2014)
Two split plot experiments were used to test the effects of three row spacings, two plant densities and two hybrids that differed only in the allelic structure of height locus 2 (Dw2 Dw2 or Dw2 dw2), on the agronomic performance of grain sorghum (Sorghum bicolor (L.) Moench). Variations in planting regimes generally were not effective in changing maturity related traits. Hybrids, however, had significant influence on days to midbloom and physiological maturation with the tall hybrid (Dw2 Dw2) showing lateness. The treatments were influential in changing plant height. Taller plants were associated with wider row spacings, the high plant density, and homozygosity at height locus 2 (Dw2 Dw2). Plants grown in rows 0,51 m apart produced the highest grain yields and the largest numbers of seeds per head and heads per plant. Conversely, the heaviest seeds were obtained at the 1,02 m row spacing. Plant density showed a consistent effect on numbers of seeds per head and heads per plant, with larger numbers observed at the low density. The allelic structure of height locus 2 affected hybrid performance for grain yield and the yield components. Homozygosity at this locus (Dw2 Dw2) consistently resulted in higher grain yields, more seeds per head and heavier seeds than did the heterozygous condition (Dw2 Dw2).
Keywords: Sorghum bicolor (L.) Moench; yield components; height genes; agronomic traits